A região cacaueira da Bahia em Jorge Amado: memória, imaginação e identidade pelo prisma da geopliteratura - Santos, Rita de Cássia Evangelista dos (2017)
In this work we approach the cocoa region of Bahia from Jorge Amado's gaze. We seek in the dialogue between geography and literature to amplify discussions on the cocoa region based on the Amadian work from the perspective of humanistic geography. The Amadian narrative on cocoa is rich in details about the formation of this portion of the Bahian space under the sign of cocoa and on the strong relationship established between the people and this crop. In this way, we start from the hypothesis that the Amadian narrative can be read geographically as a lived space, capable of offering the cocoa region of Bahia an identity, the grapiúna identity and this narrative is also generating and feeding a social imaginary, spreading this region while a cultural region. It is also discussed the displacement of this region through the Amadian narrative amplifying this imaginary. The analysis was constituted from the works O menino grapiúna (1982), Terras do Sem Fim (1943) and São Jorge dos Ilhéus (1944).These works together, compose an interesting narrative about the referred region based on the author's memory and experience. Based on the analysis of this narrative, it was possible to identify a regional formation based on violence and dismantling. At the same time, it was identified a strong relationship between the people with the land and the cocoa. Jorge Amado, through his narrative, lets rise, even in the tensions of daily life, a topofilia from the characters that, in some way, is also his own topofilia and mine. We use as a methodological course the interpretation of the literary text, letting it speak in its own way, correlating it with the scientific discourse.